Oscillatory flow of casson fluid between parallel plates with an inclined magnetic field - Rafiuddin, Rafiuddin; Ghouri, Noushima (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The study of heat and mass transfer of oscillatory casson flow in porous medium subject to an inclined magnetic field, radiative heat flux and heat source is presented. It is supposed that Casson fluid is little conductive and produced emf is insignificant. The solutions of coupled partial differential equations of velocity, temperature and con- centration profiles are found using Galerkins technique of finite element method. The effect of various parameters such as Reynolds number Re, Grashoff number Gr, Solute Grashoff number Gc, Peclet number Pe, Hartman number Ha, Scmidth number Sc, Permeability parameter K, Radiative parameter R, Heat generation parameter S, Chemical reaction parameter Kr and frequency parameter w on velocity, temperature and concentration are shown graphically and skin friction, Nusselts number and Sherwood number are discussed by tables.